Mechanisms of trematodiases pathogenicity: the presence of the secretory proteins from the liver fluke Opisthorchis felineus in the gallbladder tissues of the patients with chronic opisthorchiasis - M. Y. Pakharukova; A. V. Kovner; A. N. Trigolubov; E. N. Fedin; E. S. Mikhailova; S. G. Shtofin; A. I. Autenshlyus; V. A. Mordvinov (Вавиловский журнал генетики и селекции)
Opisthorchiasis caused by the liver fluke Opisthorchis felineus infection remains a serious public health problem in the former USSR and Eastern European countries. O. felineus infests the bile ducts, the liver and gallbladder of many fish-eating mammalian species, including humans. Opisthorchiasis leads to a number of related diseases of the liver and pancreas: liver fibrosis, cholangitis, cholecystitis, liver cysts and pancreatitis. Excretory-secretory products of the parasite are considered to be key factors in host-parasite relationships and mediate pathogenic pleiotropic effects on the host organism.The aim of this study was to determine the helminthic proteins (thioredoxin peroxidase and glutathione-S-transferase) in the gallbladder tissues of the experimental animals and patients with opisthorchiasis disease. We demonstrated by immunohistochemistry assay using antibodies against recombinant O. felineus proteins that thioredoxin peroxidase and glutathione-S-transferase could be detected in the biliary duct epithelium of the experimental animals and in human gallbladder tissues. Moreover, these proteins could also be detected in human gallbladder infiltrated cells and underlying connective tissues. The results are important for understanding the molecular mechanisms of opisthorchiasis pathogenesis, as well as for improvement of the immunodiagnostics of the opisthorchiasis and opisthorchiasis-related diseases.